CHARACTERIZATION OF ANTIOXIDANT COMPOUNDS FROM CELEBES SEA BAMBOO EXTRACTS (Isis hippuris) USING GC-MS - Tanod, Wendy Alexander; Dewanto, Didit Kustantio; Cahyono, Eko; Ansar, Novalina Maya Sari; Rieuwpassa, Frets Jonas; Sambeka, Yana (Jurnal Perikanan dan Kelautan, 2023)
Sea bamboo (Isis hippuris) is one of the octocorallia which is reported to produce unique biological activity and is beneficial for pharmaceutical development. Evaluation of the bioactive compounds of sea bamboo collected from Sulawesi (Celebes) waters has never been reported. Gas chromatography and mass spectrometry (GC-MS) are convenient methods for evaluating bioactive compounds. This study aims to evaluate bioactive compounds from extracts of sea bamboo from Sulawesi by GC-MS method and predict their activity computationally. Samples of sea bamboo were collected from Kabonga Besar Coast, Palu Bay, Central Sulawesi, Indonesia. Samples were extracted by maceration method using methanol: dichloromethane solvent. GC-MS evaluated bioactive compounds from sea bamboo extracts. The antioxidant activity was determined by the DPPH scavenging method, compared with Vitamin E. The biological activity of Celebes sea bamboo extracts was predicted with PASS prediction. GC-MS evaluation identified nine alkaloid-derived and phenolic-derived compounds, namely tetramethyldiaminoethane; dimethylisopropanolamine; crotonic acid, (E)-; 2,4-dimethylpyrrole; 1-(carboxymethyl)pyridinium chloride; pyridine, 3,4-dimethyl-; 3,5-dithiahexanol 5,5-dioxide; N-Nitroso-2-methylthiazolidine; and (-)-cis-carveol. The Celebes sea bamboo extracts have strong antioxidant activity. These compounds are predicted to have antioxidant abilities, closely related to their role as NADPH-oxidase inhibitors.